Evaluation of the Global Lung Function Initiative 2012 reference values for spirometry in an Iranian population - Leyla Sahebi; Besharat Rahimi; Mamak Shariat; Seyyed Hosein Mousavy (Scientific Reports, 2022)
Abstract Spirometry is an important measurement in detecting and monitoring of chronic obstructive pulmonary disease. The validity of the multi-ethnic Global Lung Function Initiative 2012 (GLI-2012) spirometric norms have been debated in some countries. The aim of the present study was to evaluate the applicability of the GLI reference norms in the Iranian population. A cross-sectional study was performed on 622 healthy non-smoker population (204 males and 418 females, age range: 4 ± 82 years) between July 16 and August 27, 2019 in Iran. Z-scores for spirometric data [FEV1 (forced expiratory volume in 1 s), FVC (forced vital capacity) FEV1/FVC, and FEF25–75% (forced expiratory flow averaged over the middle portion of FVC)] were calculated. According to the agreement approved, a mean Z-score outside the range of ± 0.5 was considered clinically significant. The mean (SD) Z-score values of FEV1, FVC, FEV1/FVC and FEF25–75% were 0.44 (1.21), 0.49 (1.14), 0.11 (1.03), and − 1.13 (0.99) in males and 0.61 (1.14), 0.89 (1.26), 0.17 (0.88) and − 0.49 (0.96) in females, respectively. The Z-score of FEV1/FVC was below the lower limit of normal (LLN) in 3.43% of men and 2.01% of women (in ≥ 21 years), while these values were significantly higher in people under 21 years old (46.2% in boys and 40.0% in girls). The GLI reference values are not perfect for the Iranian population, especially in children below 10 years old. The use of the GLI reference values was appropriate in population above 21 years; however, they would overestimate the prevalence of airway obstruction in individuals below 21 years.